Giovanni Patroni e l’opposizione a Luigi Pigorini - Pearce, Mark (Istituto italiano di preistoria e protostoria, 2015)
Giovanni Patroni e l’opp osizione a Luigi Pigorini - Giovanni Patroni (1868-1951) is notorious for a virulently anti-communist passage describing the inhabitants of the Terramare, which appears in his La Preistoria d’Italia (2 vols, Milan, 1937). He is also an important figure in the history of Italian prehistoric archaeology who is worth remembering as the author of the first major synthesis of Italian prehistory (La Preistoria d’Italia), for his courage in daring to oppose the ideas of Pigorini even before Pigorini died, and as the founder of the Milan School of prehistoric studies. Patroni first major contribution was his La ceramica antica nell’Italia meridionale (Naples, 1897), in which, in disagreement with the majority view in Europe, according to which Apulian red-figure pottery was made at Taras, he argued that it was more likely that it was made in the indigenous settlement of Ruvo di Puglia. This publication highlights the two sides of Patroni - his polemical nature and his nationalistic preference to explain archaeological phenomena as having developed locally. In 1901 he was appointed Professor of Archeology at the University of Pavia, and in parallel Archaeological Superintendent for Lombardy from 1905 to 1924; in 1927 he transferred to the newly-founded State University of Milan and retired in 1938. In this paper I explore the early years of Patroni’s scientific activity, when as a convinced Mediterraneanist, he opposed Pigorini’s ideas. I discuss his publications during the period he worked at the University of Pavia and the development of his ideas concerning the Terramare, with particular attention to the excavations at Cella Dati, Castellaro del Vhò di Piadena and San Pietro in Mendicate. I also discuss his famous reactionary description of the life of the inhabitants of the Terramare, which betrays his rather unsavoury political views but also throws light on his formation in the idealist environment of late nineteenth-century Naples.